Fear Appeal dan Batasan Etika dalam Iklan Digital: Studi Kasus Iklan Podcast Horor Spotify - Vanessa Harjanto; Priya Anka Anjely; Daniel Nathan Asuncion Tjie; Muhammad Axel Zulchair; Dimas Prasetyo Nugroho; Nicko Setiawan (Journal of Innovative and Creativity, 2025)
The fear appeal strategy, or a fear-based persuasive approach, has long been employed in marketing communication. In the digital era, this technique has evolved and is now utilized across various advertising formats, including podcasts on Spotify. This study aims to examine the use of fear appeal in Spotify horror podcast advertisements, focusing on ethical communication practices. This study employs a descriptive qualitative approach using literature-based content analysis, with data synthesized from academic journals, news articles, and relevant scholarly sources.to understand how fear appeal is applied and its impact on the audience. The primary focus is to ethically evaluate the distinctions between persuasion and manipulation in digital advertising. This study applies normative ethical theories—Theory of Rights, Utilitarianism, and Theory of Justice—to examine whether the use of fear in advertisements is morally justifiable. The findings are expected to provide insights and promote ethical considerations in digital marketing practices.